2019
DOI: 10.3386/w25919
|View full text |Cite
|
Sign up to set email alerts
|

Trade and Worker Deskilling

Abstract: This paper presents new evidence on international trade and worker outcomes. It examines a big world event that produced an unprecedentedly large shock to the UK exchange rate. In the 24 hours in June 2016 during which the UK electorate unexpectedly voted to leave the European Union, the value of sterling plummeted. It recorded the biggest depreciation that has occurred in any of the world's four major currencies since the collapse of Bretton Woods. Exploiting this variation, the paper studies the impact of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 58 publications
1
31
0
Order By: Relevance
“…4 Papers documenting a negative impact of Brexit on UK investments, employment, wages, trade, lending, and competition include Born et al (2019); Berg et al (2019); Van Reenen (2016); Sampson (2017);Breinlich et al (2018); Davies and Studnicka (2018); Dhingra et al (2017); Graziano et al (2018); Garetto et al (2019); Costa et al (2019); McGrattan and Waddle (2017); Steinberg (2019). 5 Campello et al (2018) document the investment and hiring e↵ects of Brexit on a sample of US firms exposed to the UK economy.…”
mentioning
confidence: 99%
“…4 Papers documenting a negative impact of Brexit on UK investments, employment, wages, trade, lending, and competition include Born et al (2019); Berg et al (2019); Van Reenen (2016); Sampson (2017);Breinlich et al (2018); Davies and Studnicka (2018); Dhingra et al (2017); Graziano et al (2018); Garetto et al (2019); Costa et al (2019); McGrattan and Waddle (2017); Steinberg (2019). 5 Campello et al (2018) document the investment and hiring e↵ects of Brexit on a sample of US firms exposed to the UK economy.…”
mentioning
confidence: 99%
“…Davidson, et al (2017) studied the skill mix demand in Sweden at the firm level and found that as firms become more globalized they tend to demand an increasing share of high-skilled occupations, supporting the geographic division of labor. Exploiting a natural experiment, the exchange rate shock caused by Brexit, Costa et al (2019) find that the falling value of the pound harmed, rather than helped, the UK's domestic workers and exporters, even leading to significant deskilling through reductions in training investments. They found that intermediate imports are complements to a significant number of domestic workers and exporters.…”
Section: Smms Focus On Jobsmentioning
confidence: 99%
“…This could suggest that firms have responded to demand by hiring rather than investing. Businesses have also absorbed some of the increased costs of imports by lowering worker wages and investment in training (Costa et al, 2019).…”
Section: Box 1 the Effects Of The Announcement Of Brexit On Economicmentioning
confidence: 99%